Core-size dispersity dominates the self-assembly of polymer grafted nanoparticles in solution - Bachhar, Nirmalya; Kurnaraswamy, Guruswamy; Kumar, Sanat K. (Macromolecules, 2019)
In polymer-grafted nanoparticles (PGN), covalent tethering of apolar polymer chains to a polar inorganic nanoparticle core induces the formation of self-assembled aggregates. Since the nature of these aggregates determines bulk mechanical and transport properties, it is of importance to understand the factors that determine the underlying assembly processes. In the literature, the solution assembly of PGNs has been understood in analogy to small-molecule amphiphiles. However, in any experimental realization, PGNs are invariably characterized by additional structural complexity, such as the distributions in the inorganic core size and in the grafted chains (both in their length and grafting density). These strongly influence the assembly of amphiphilic PGNs. We have previously demonstrated that dispersity in core size qualitatively affects the structure of PGN aggregates, and Jayaraman et al. demonstrated the effect of grafted chain-length dispersity. The combined effects of dispersity in the size of the core and grafted chains have not been explored previously. Here, we develop a model that builds on the work of Daoud and Cotton to explore a wide parameter space of PGN with dispersity simultaneously in core size and grafted chain length. We demonstrate that dispersity in core size is the dominant factor affecting the self-assembled solution structure of PGN aggregates. Our work suggests the importance of focusing on synthetic strategies for control of core-size dispersity to control aggregate structure in PGN.

Three-dimensional printing with waste high-density polyethylene - Gudadhe, Aniket; Bachhar, Nirmalya; Kumar, Anil; Andrade, Prem; Kumaraswamy, Guruswamy (ACS Applied Polymer Materials, 2019)
Fused filament fabrication (FFF) three-dimensional (3D) printing of semicrystalline polymers such as high density polyethylene (HDPE) is challenging because crystallization-induced shrinkage of the filament, as it cools, results in stresses that warp the printed part and debond it from the print substrate. Here, we demonstrate that waste-derived HDPE can be successfully 3D printed by (i) blending with a small fraction (<0.5% by weight) of dimethyl dibenzylidene sorbitol (DMDBS) and (similar to 10%) linear low density polyethylene (LLDPE) and (ii) printing the object with a thin ``brim'' around it that is adhered to the print substrate using common polyvinyl acetate-based glue. We match our experimental results with FEM simulations that provide insight into the origin of the stresses developed during printing. Because HDPE forms a significant fraction of the plastic waste stream, conversion of waste-derived HDPE to 3D printing filament has important technological implications.
Keywords: 3d printing polyethylene printing; polymer blend; Recyclability; warpage

3D printing of semicrystalline polypropylene: towards eliminating warpage of printed objects - Bachhar, Nirmalya; Gudadhe, Aniket; Kumar, Anil; Andrade, Prem; Kumaraswamy, Guruswamy (Bulletin of Materials Science, 2020)
Fused filament fabrication (FFF) is an extrusion-based 3D printing technique for thermoplastic polymers. In this technique, molten polymer is extruded through a print nozzle and is laid down layer by layer to build up the printed object. Currently, FFF is used primarily to print amorphous or low-crystallinity polymers, such as acrylonitrile butadiene styrene copolymer (ABS) or polylactic acid (PLA). Printing of semicrystalline polymers, such as polyethylene or polypropylene remains particularly challenging. During FFF of semicrystalline polymers, large thermomechanical stresses are generated when the polymer solidifies on cooling. These stresses result in warpage of the printed part. Here, we analyse the factors that influence stresses generated during FFF 3D printing of a commercial semicrystalline polymer, isotactic polypropylene. We investigate the effect of height of the printed object on part warpage, as well the effect of infilling during printing. We demonstrate that the stresses generated during FFF can be substantially decreased by incorporation of a `brim', viz. a thin layer at the base of the printed object, and by adhering the brim to the print substrate using common polyvinyl acetate-based glue. We systematically investigate the effect of the brim size on the warpage of the printed object. We support our experimental findings with finite element method (FEM) simulations that explain the mechanism of stress buildup during printing. The trend in stresses calculated in the FEM simulations parallel the warpage measured in the experiments. Thus, this work represents an important methodological advance towards warpage-free FFF printing of semicrystalline polymers.
Keywords: 3D printing; polypropylene printing; warpage

Polyethylene-grafted sheet-like silsesquioxane nanocomposites with unprecedented adhesion to polar substrates - Sharma, Vivek; Paulbudhe, Uday; Bachhar, Nirmalya; Chikkali, Samir H.; Kumaraswamy, Guruswamy (ACS Applied Polymer Materials, 2023)
Polyethylene is a highly apolar polymer with very pooradhesionto most substrates, necessitating the use of tie layers. Therefore,the synthesis of functional polyethylene is a long-standing challengein catalytic ethylene polymerization. Here, we report the preparationof a nanocomposite comprising polyethylene covalently grafted ontosheet-like silsesquioxanes, with unprecedented adhesion to metal andglass. A norbornene-grafted, layered Mg-silsesquioxane is treatedwith Grubbs second-generation catalyst (G-II), and the identity ofcovalently tethered G-II is unambiguously ascertained. Covalentlytethered G-II catalyzes the ring opening metathesis polymerizationof cyclooctene to poly(cyclooctene). The resulting poly(cyclooctene)is catalytically hydrogenated to yield polyethylene. This polyethylenenanocomposite exhibited a bonding strength of the order of 100 MPaon stainless steel and aluminum, 10-fold higher than reported forengineered polyethylene copolymers. The nanocomposite exhibits anincrease in the polar component of surface energy, yet remains compatibleand cocrystallizes with a polyethylene matrix.
Keywords: adhesion; clay; Nanocomposite; Polyethylene; silsesquioxane